Uji Validitas Modul Pertumbuhan dan Perkembangan Berbasis Potensi Lokal untuk Siswa SMA Negeri 1 Afulu - Jun Mardin Telaumbanua; Hardikupatu Gulo; Nofamataro Zebua (Program Studi Pendidikan Biologi - Universitas Nias, 2023)
This study aims to develop a plant growth and development module based on local resources for students at SMA Negeri 1 Afulu and to test its validity. The instrument used was a validity questionnaire consisting of didactic criteria, construct validity criteria, technical criteria, and linguistic criteria. The validity questionnaire was evaluated by three experts in their respective fields. The didactic criteria received a score of 89.58%, the construction criteria received a score of 87.87%, the technical criteria received a score of 85.41%, and the language criteria received a score of 89.58%. All validity criteria fell into the “highly valid” category. The plant growth and development module based on local potential has been successfully developed and can increase students’ awareness of the local potential in their area, so that students not only learn but also gain essential values from the learning process.